MODEL REPRESENTING THE RELATIONSHIP BETWEEN THE SOIL ATRIBUTES AND THE PRODUCTION OF SUGARCANE USING STRUCTURAL EQUATIONS - ARAÚJO, Elton Gean; CARVALHO, Morel de Passos e; MONTANARI, Rafael; ANDREOTTI, Marcelo; CARDOZO, Nilceu Piffer; PANOSSO, Alan Rodrigo (Brazilian Journal of Biometrics, 2018)
The sugarcane is the main source of renewable energy in Brazil and it is considered that this crop has an economically as well as environmentally promising future around the world. This fact justifies the researches regarding the comprehension of its behaviour in the soil-plant system. This study aimed to explain the productivity of the sugarcane crop through latent factors formed from chemical and physical attributes of an Ultisol with a medium/clayey texture using the technique of structural equations modelling. In order to collect the data of the plant as well as the soil, we defined 118 sampled points of a regular grid in the depths of 0 to 0.20 m and from 0.20 to 0.40 m. The first three factors composed the chemical, physical and production attributes explaining around 60% of the data variability. The technological and production components of the sugarcane were negatively influenced by the physical attributes factor from 0 to 0.20 m. However, there was a positive influence of the chemical attributes factor associated with the acidity in the layer from 0.20 to 0.40 m.